Immunomodulatory properties of morphine and the hypothesised role of long-term opioid use in the immunopathogenesis of tuberculosis - Bataduwaarachchi, Vipula R.; Hansanie, SMN; Rockwood, Neesha; D'Cruz, Leon Gerard (Frontiers in Immunology, 2023)
Epidemiological studies have shown high tuberculosis (TB) prevalence among chronic opioid users. Opioid receptors are found on multiple immune cells and immunomodulatory properties of opioids could be a contributory factor for ensuing immunosuppression and development or reactivation of TB. Toll-like receptors (TLR) mediate an immune response against microbial pathogens, including Mycobacterium tuberculosis. Mycobacterial antigens and opioids co-stimulate TLRs 2/4/9 in immune cells, with resulting receptor cross-talk via multiple cytosolic secondary messengers, leading to significant immunomodulatory downstream effects. Blockade of specific immune pathways involved in the host defence against TB by morphine may play a critical role in causing tuberculosis among chronic morphine users despite multiple confounding factors such as socioeconomic deprivation, Human immunodeficiency virus co-infection and malnutrition. In this review, we map out immune pathways involved when immune cells are co-stimulated with mycobacterial antigens and morphine to explore a potential immunopathological basis for TB amongst long-term opioid users.